2012
DOI: 10.1017/s1368980012001103
|View full text |Cite
|
Sign up to set email alerts
|

Sales effects of product health information at points of purchase: a systematic review

Abstract: Objective: Information about healthy and unhealthy nutrients is increasingly conveyed at the point of purchase. Many studies have investigated the effects of product health information on attitudes and intentions, but the empirical evidence becomes sketchier when the focus of research is actual purchase behaviour. The present paper provides an overview of empirical evidence on the effectiveness of product health information for food products at the point of purchase. Design: A systematic literature review was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 55 publications
1
43
1
Order By: Relevance
“…Whether consumers actually use FOP nutrition labels has been examined by analyzing sales data (e.g., Van 't Riet, 2013). By analyzing purchasing data over a period of two years, the Guiding Star systems showed significant but small changes in food purchasing immediately after implementation, and these changes continued to be significant even after two years (Sutherland et al, 2010).…”
Section: Use In Stores and Impact On Consumer Diet And Healthmentioning
confidence: 99%
“…Whether consumers actually use FOP nutrition labels has been examined by analyzing sales data (e.g., Van 't Riet, 2013). By analyzing purchasing data over a period of two years, the Guiding Star systems showed significant but small changes in food purchasing immediately after implementation, and these changes continued to be significant even after two years (Sutherland et al, 2010).…”
Section: Use In Stores and Impact On Consumer Diet And Healthmentioning
confidence: 99%
“…On the other hand higher fast-food prices and lower fruit and vegetables prices were associated with lower weight outcomes. The eighth review [12] aimed to assess the effectiveness of providing food product health information at the point of purchase. This review included 16 articles (reporting on 17 studies) that derived their outcome measure from point-of-sale data.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported no significant effects of product health information on actual purchase behaviour. Interventions were more likely to be effective when they lasted for a longer time, when they included additional intervention components, and when they targeted the absence of unhealthy nutrients instead of or in addition to the presence of healthy nutrients [12]. …”
Section: Introductionmentioning
confidence: 99%
“…Nutrition information systems provide health-related food and nutrient information to consumers, usually at the point of purchase, in the form of labels on products or shelves (12)(13)(14)(15) . Such information can operate in several ways, including influencing the purchase of nutritious foods (12) (e.g.…”
mentioning
confidence: 99%